The path to paradise the inner world of suicide bombers and their dispatchers - Berko, Anat (Potomac Books, 2009)
Suicide bombers are often compared to smart bombs. What are their thought processes? Do male bombers really believe that death will transport them to a paradise inhabited by virgins? What are female bombers promised in the hereafter? This title focuses on exploring the inner world of suicide bombers.